Understanding Intimate Relationships with Abusive Behavior Through Attachment Theory - de Souza Tosta, Amanda; Cassepp-Borges, Vicent (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2021)
This work aims to understand abusive relationships through the Attachment Theory, addressing the concept of violence, which types of violence within intimate relationships (Physical, Sexual, Verbal and Psychological), statistical explanations and correlations between the causes of violence abusive behaviors and the effects on the lives of those who suffer them. Participating in this study were 464 women and 85 men, responding to the Experiencie in Close Relationships (ECR), Intimate Relationship Abuse Scale (ARI) and Intimate Relationship Abuse based on respondent behavior in relation to the other (ARI-E) and a demographic questionnaire by electronic means. The results indicated that the ARI and ECR scales present good psychometric properties. With regard to violence suffered, women reported experiencing significantly greater physical violence than men, while men reported experiencing psychological violence and controlling attitudes significantly higher than women. This study suggests that the ARI scale has good indicators of validity and reliability in assessing intimate relationship violence.